Exploring Guilt, Trauma, and Redemption: A Psychoanalytic Study of Silent Hill 2’s Dialogue and Monologue - Baihaqi, Zulfan Rafly; Syarifudin, Bunyamin Faisal; Nurulaen, Yuyun (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2025)
This study examines Silent Hill 2 through Freud’s psychoanalytic theory, analyzing how James Sunderland’s dialogues and monologues reflect guilt, trauma, and redemption. The findings reveal that denial, projection, and repression manifest in his interactions, shaping his psychological struggle. The game’s symbolic environment externalizes his unconscious conflicts, reinforcing its narrative depth. This research underscores the potential of video games as a medium for exploring complex psychological themes and contributes to interdisciplinary discussions in psychoanalysis, literary studies, and media studies.